The use of inhibitors of fibrinolysis in the treatment of obstetric hemorrhage due to placenta detachment - Irina A. Lyoshenko; Oleg O. Tarabrin; Maxim Y. Holubenko; Dmitry G. Havrichenko (Kazimierz Wielki University, 2016)
Lyoshenko I. A., Tarabrin O. A., Holubenko M. Yu., Havrichenko D. H. The use of inhibitors of fibrinolysis in the treatment of obstetric hemorrhage due to placenta detachment. Journal of Education, Health and Sport. 2016;6(1):129-137. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44836 http://ojs.ukw.edu.pl/index.php/johs/article/view/44836 https://pbn.nauka.gov.pl/works/696071           The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 20.01.2016.     UDC: 616-00 5.1: 616-006.6     The use of inhibitors of fibrinolysis in the treatment of obstetric hemorrhage due to placenta detachment     I. A. Lyoshenko, O. A. Tarabrin, M. Yu. Holubenko, D. H. Havrichenko     Odessa State Medical University, Odessa, Ukraine     Authors: Tarabrin Oleg Oleksandrovych - MD, prof., Head of the department of anesthesiology and Intensive care of ONMedU, Odessa Regional Clinical Hospital, t. 7500372 Holubenko Maxim Yuriyovych - MD, maternity home №2 Odessa, head doctor, t. 7311486 Havrichenko Dmitry G., - Ph.D., Department of IC and anesthesiology of ONMedU, assistant, t. 7500372 Lyoshenko Irina Anatoliyivna - maternity home №2 Odessa, anesthesiologist, t. 0679378848, t. 0661705012, e-mail: irenodessa5555@gmail.com   Abstract Purpose. Comparative evaluation of efficacy of aprotinin and tranexamic acid for the influence on the system of hemostasis, fibrinolysis, and the blood loss degree. Results. There were studied the results of fibrinolysis inhibitor therapy in women undergoing cesarean section for premature detachment of the placenta. The condition of hemostasis was controlled by low-frequency piezoelectric thromboelastography. There were obtained data on a more pronounced antifibrinolytic and blood preserving effect of the tranexamic acid, which was reflected in the reduction of the intraoperative, general and postoperative blood loss in group of tranexamic acid by 19.8%, 13.4% and 47.6%. The need for transfusion was also the lowest in the group with the tranexamic acid, which showed its greatest "blood preserving" effect. Conclusions. Early use of inhibitors of fibrinolysis in premature detachment of the placenta is pathogenetically justified and necessary, allowing to reduce the perioperative blood loss. Using low-frequency piezoelectric thromboelastography  in obstetric bleeding makes it possible to detect quickly and reliably disorders in various levels of hemostasis, allowing to carry out their correction timely and fully.   Keywords: premature detachment of the placenta, hemostasis, fibrinolysis, aprotinin, tranexamic acid.